Teacher’s Strategy in Improving Reading Comprehension Skills of Arabic Texts at Madrasah Ibtidaiyah - Masnun, Moh; Putri, Alvy Salmia; Jaelani, Aceng; Ummah, Inayatul (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis study aims to describe the teacher's strategy for improving reading comprehension skills of Arabic texts in class v at Madrasah Ibtidaiyah (Islamic Elementary School) in Cirebon City. This qualitative research uses a descriptive approach. The sources of data or informants in this research are Arabic teachers, fifth-grade students, and school principals. The data were collected through observation, in depth-interviews and documentation. Data analysis starts with data reduction, presentation, and interpretation. The results showed that the Arabic teacher's strategies in improving reading comprehension skills of Arabic texts in class V were as follows: 1. Reading texts Aloud, 2; translating texts, 3. Reviewing translation results, 4, Answering questions, 5. Sharing answers, and 6. Repetition. Arabic text comprehension reading skills in class V are quite good, obtaining an average score that has met the minimum completeness criteria. The teacher and student experienced during the learning process reading comprehension skills in Class V supported by the activity of reading the Holy Qur'an every Monday to Thursday, which is carried out after learning activities, recitation activities at home with a teacher of the Qur'an, the availability of a library at school, and studying with peers. Then some of the difficulties faced are the lack of parental support, the habits of students who often play with gadgets, and the lack of availability of book facilities in the library.Keywords: teacher strategy, reading comprehension skills, Arabic text.AbstrakPenelitian ini bertujuan untuk mendeskripsikan strategi guru dalam meningkatkan keterampilan pemahaman membaca teks bahasa Arab di kelas V di salah satu Madrasah Ibtidaiyah di Kota Cirebon. Penelitian kualitatif ini menggunakan pendekatan deskriptif. Sumber data atau informan dalam penelitian ini adalah guru bahasa Arab, siswa kelas V, dan kepala sekolah. Pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi. Data yang dianalisis dimulai dari reduksi data, penyajian data, dan interpretasi data. Hasil penelitian menunjukkan bahwa strategi guru bahasa Arab dalam meningkatkan keterampilan pemahaman membaca teks bahasa Arab di kelas V adalah sebagai berikut; 1. membaca teks dengan keras, 2. menerjemahkan teks, 3. menelaah hasil terjemahan, 4, menjawab pertanyaan, 5. berbagi jawaban, dan 6. pengulangan. Keterampilan membaca pemahaman teks bahasa Arab pada siswa kelas V sudah cukup baik dengan memperoleh nilai rata-rata yang telah memenuhi kriteria ketuntasan minimal. Pengalaman guru dan siswa selama proses pembelajaran keterampilan membaca pemahaman di Kelas V didukung dengan adanya kegiatan membaca Al-Qur'an setiap hari senin sampai dengan kamis yang dilaksanakan setelah kegiatan pembelajaran, kegiatan pengajian di rumah bersama guru mengaji, dan tersedianya perpustakaan di sekolah, serta belajar bersama teman sebaya. Kemudian beberapa kendala yang dihadapi adalah kurangnya dukungan orang tua, kebiasaan siswa yang sering bermain gadget, dan kurangnya ketersediaan fasilitas buku di perpustakaan.Kata kunci: strategi pembelajaran, keterampilan membaca pemahaman, teks